Space and ground-based investigations of dayside reconnections: Cluster, double star and superdarn observations - Wild,JA; Milan,SE; Davies,JA; Cowley,SWH; Dunlop,MW; Owen,CJ; Bosqued,JM; Lester,M; Balogh,A; Carr,CM; Fazakerley,AN; Rème,H (2006)
In this paper, we present an overview of several investigations that have exploited Cluster, Double Star and SuperDARN radar data in order to scrutinise the coupling of the solar wind, magnetosphere and ionosphere. The studies introduced have drawn upon simultaneous space- and ground-based data in order to overcome the inherent shortcomings of the in situ (space-based) and remotely-sensed (ground-based) measurement techniques. In particular, we shall highlight the results of studies that investigate the dynamics arising from magnetic reconnection at the dayside magnetopause and the resulting ionospheric responses.